Controller Design for Input-Saturated Discrete-Time Switched Systems with Stochastic Nonlinearity - Wang, Qian; Lin, Qingxia (Circuits, systems, and signal processing, 2023)
In this paper, we study the mean-square exponential stability of the input-saturated discrete-time switched systems with stochastic nonlinearity. The main contributions are as follows: (1) Based on the low-gain feedback control and the discrete parametric Lyapunov equation, a state feedback controller and an output feedback controller are designed; (2) the input saturation and stochastic nonlinearity are solved; and (3) the stability of the system is analyzed and the closed-loop system is mean-square exponentially stable under the designed controllers. The validity of the theoretical results is verified by the numerical simulations.